2006
DOI: 10.1017/s0021121400004892
|View full text |Cite
|
Sign up to set email alerts
|

Football and sectarianism in Glasgow during the 1920s and 1930s

Abstract: Of all the cities of England and Scotland, Glasgow is most widely associated with sectarianism. As Bill Murray has remarked, the city is renowned for its religion, violence and football, three elements which crystallise in the uniquely bitter encounters between the city’s two major football clubs, Rangers and Celtic. The clubs are identified as ‘Protestant’ and ‘Catholic’ respectively, although, as Tom Gallagher has commented, supporters’ allegiances tend to be more tribal than doctrinal. Religion is inextrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…There are other factors as well which can contribute or act independently such as segregation based upon a general socioeconomic status as presented in 9 which looks at European cities and 10 that examines Latin American cities. The separating label which residents can use to differentiate themselves can be placed upon football team support as shown in the Glasgow (UK) history of sectarianism between teams Celtic and Rangers 11 . The work of 12 looks at some of the real world complex patterns displayed by segregation upon ethnic and religious statuses in which a utility (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are other factors as well which can contribute or act independently such as segregation based upon a general socioeconomic status as presented in 9 which looks at European cities and 10 that examines Latin American cities. The separating label which residents can use to differentiate themselves can be placed upon football team support as shown in the Glasgow (UK) history of sectarianism between teams Celtic and Rangers 11 . The work of 12 looks at some of the real world complex patterns displayed by segregation upon ethnic and religious statuses in which a utility (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, other research challenges both the primacy of schooling to the construction of social networks and the extent of sectarianism within and beyond the spaces of urban education. Recent research on gangs in Glasgow found that they formed on the basis of geographical territory and not religion or football affiliation and that neither religion or football affiliation would form a barrier to friendships (Deuchar & Holligan, 2010; see also Davies, 2006, for similar historical findings). Rather, the main rivalry is between housing schemes, and this territorial basis for identity and conflict meant that Celtic and Rangers supporters (and Catholics and Protestants) often come together to form friendships within gangs (Seith, 2008;Deuchar & Holligan, 2010; see also Clayton, 2009, for the importance of neighbourhood territorial rivalries influencing racial and ethnic interaction within and outside schools).…”
Section: The Specific Context Of (In)visible Difference In Glasgow Anmentioning
confidence: 94%
“…However, the relationship between loyalist and republican bands in Scotland and Northern Ireland is beyond the scope of this article. 17 See McKerrell 2012Davies 2013; official definition as to what constitutes a 'sectarian song', neither is there an authoritative definition of 'Irish rebel music'; it has no place in The New Grove Dictionary of Music and Musicians or the Oxford Dictionary of Music, a testament to its underground, underresearched, and under-valued nature within the academy.…”
Section: What Is Irish Rebel Music?mentioning
confidence: 99%
“…10 Further, although singing sectarian songs in public is now illegal in Scotland, there has been no official definition as to what actually constitutes a 'sectarian song' and so it is left to the police to exercise their discretion in the matter (Waiton 2012:40-41). While some have focused on the use and interpretation of anti-Catholic music in Scotland (McFarland 1990;McKerrell 2012Davies 2013;Millar 2015), there has 6 In a previous attempt to tackle sectarianism in Scotland, the Scottish Labour-led Government introduced a new statutory aggravation under Section 74 of the Criminal Justice (Scotland) Act 2003. This enabled an existing offence to be treated as having been aggravated by religious prejudice.…”
mentioning
confidence: 99%